The role of international assignees' social capital in creating inter-unit intellectual capital: A cross-level model - Reiche, B Sebastian; Harzing, Anne-Wil; Kraimer, Maria L (Journal of International Business Studies, 2009)
We conceptualize international assignees as informational boundary spanners between multinational enterprise units, and develop a cross-level model that explores how assignees' social capital translates into inter-unit intellectual capital. First, as knowledge brokers, assignees create inter-unit intellectual capital by linking their home- and host-unit social capital, thereby enabling cross-unit access to previously unconnected knowledge resources. Second, as knowledge transmitters, assignees' host-unit social capital facilitates their creation of individual intellectual capital, which, in turn, translates into inter-unit intellectual capital. We conclude that individual social capital needs to be explicitly transferred to the organizational level to have a sustained effect on inter-unit intellectual capital.